RUANG MASYARAKAT ADAT DALAM PEMANASAN GLOBAL DAN PERUBAHAN IKLIM KASUS PROGRAM REDD+ DI KALIMANTAN TENGAH - Sidik R Usop (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2012)
Global warming and climate change are caused by increased in the greenhouse gases emission. Deforestation is one of the main contributors of the increased in greenhouse gases emission. In Central Kalimantan, deforestation has caused massive forest ? re, water depletion and people being marginalized. There is a need for a mitigation strategy to protect people in this area from the adverse effect of global warming and climate change.The National program for REDD+ was piloted in Central Kalimantan to provide showcase of deforestation mitigation measures and improving communitys welfare. The key element in the implementation of REDD+ in Central Kalimantan is the active participation, especially the indigenous people, in developing social and environment safeguard system. The indigenous people have been resisting to be marginalized and isolated from natural resource extractions. They often used cultural attributes for social movement when formal dialogue failed. In some cases, they used head hunter for restoring their cultural honor. For the indigenous people, land right, cultural values and local wisdom are key principles for sustaining natural resource utilization. The violation against these three principles often leads to social con? ict and violence. Therefore, it is necessary to consider the three issues in the development agenda in this area. In addition, it is also important to understand the culture of the indigenous community, and to develop their capacity to create local wisdom.Keywords: Penduduk asli, gerakan sosial, kon? ik, pemanasan global